Synthesis of Flavonoids or Other Nature-Inspired Small Molecules - Ribaudo, Giovanni (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue aims to provide an updated overview of the flourishing ongoing research activity in the field of the chemistry of natural and nature-inspired compounds. Ten of the submitted articles were accepted for publication after peer-review. Interestingly, the published papers cover a wide range of chemical reactions, different scaffolds, and several medicinal chemistry applications. Moreover, this Special Issue gathered contributions from all over the world, testifying the international scientific community's interest in this topic. I would like to sincerely thank the MDPI staff, particularly Jade Lu and the editorial team of Molbank. I am particularly grateful to the authors that decided to share the results of their research by contributing their manuscript to this Special Issue, and, of course, to the reviewers for their valuable help.